The effects of nitrate ingestion on high-intensity endurance time-trial performance: A systematic review and meta-analysis - Tak Hiong Wong; Alexiaa Sim; Stephen F. Burns (Elsevier, 2022)
Background/Objective: Dietary nitrate ingestion extends endurance capacity, but data supporting endurance time-trial performance are unclear. This systematic review and meta-analysis evaluated the evidence for dietary nitrate supplementation to improve high-intensity endurance time-trial performance over 5-30 min on the premise that nitrate may alleviate peripheral fatigue over shorter durations. Methods: A systematic literature search and data extraction was carried out following PRISMA guidelines and the PICOS framework within five databases: PubMed, ProQuest, ScienceDirect, Scopus and SPORTDiscus. Search terms used were: (nitrate OR nitrite OR beetroot) AND (high intensity OR all out) AND (time trial or total work done) AND performance. Results: Twenty-four studies were included. Fifteen studies applied an acute supplementation strategy (4.1 mmol-15.2 mmol serving on one day), eight chronic supplementation (4.0 mmol-13.0 mmol per day over 3-15 days), and one applied both acute and chronic supplementation (8.0 mmol on one day and over 15 days). Standardised mean difference for time-trial ranging from 5 to 30 min showed an overall trivial effect in favour of nitrate (Hedges'g = 0.15, 95% CI -0.00 to 0.31, Z = 1.95, p = 0.05). Subgroup analysis revealed a small, borderline effect in favour of chronic nitrate intervention (Hedges'g = 0.30, 95% CI -0.00 to 0.59, Z = 1.94, p = 0.05), and a non-significant effect for acute nitrate intervention (Hedges'g = 0.10, 95% CI -0.08 to 0.28, Z = 1.11, p = 0.27). Conclusion: Chronic nitrate supplementation improves time-trial performance ranging from 5 to 30 min.